2008
DOI: 10.1073/pnas.0710736105
|View full text |Cite
|
Sign up to set email alerts
|

Mms19 protein functions in nucleotide excision repair by sustaining an adequate cellular concentration of the TFIIH component Rad3

Abstract: Nucleotide excision repair (NER) is a major cellular defense mechanism against DNA damage. We have investigated the role of Mms19 in NER in the yeast Saccharomyces cerevisiae. NER was deficient in the mms19 deletion mutant cell extracts, which was complemented by the NER/transcription factor TFIIH, but not by purified Mms19 protein. In mms19 mutant cells, protein levels of the core TFIIH component Rad3 (XPD homologue) and Ssl2 (XPB homologue) were significantly reduced by up to 3.5-and 2.2-fold, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…In addition, MMS19 (a cytosolic iron-sulfur cluster assembly protein) associates with XPD in the cytoplasmic iron-sulfur cluster assembly (CIA) complex (128), which plays a central role in DNA metabolism and the maintenance of genomic integrity (129)(130)(131). Interestingly, MMS19 inactivation strongly reduces the iron incorporation in XPD and consequently its cellular concentration (132,133), a phenomenon also observed when the 4Fe-S domain of XPD is mutated.…”
Section: Xpd In Other Partnershipsmentioning
confidence: 89%
“…In addition, MMS19 (a cytosolic iron-sulfur cluster assembly protein) associates with XPD in the cytoplasmic iron-sulfur cluster assembly (CIA) complex (128), which plays a central role in DNA metabolism and the maintenance of genomic integrity (129)(130)(131). Interestingly, MMS19 inactivation strongly reduces the iron incorporation in XPD and consequently its cellular concentration (132,133), a phenomenon also observed when the 4Fe-S domain of XPD is mutated.…”
Section: Xpd In Other Partnershipsmentioning
confidence: 89%
“…First of all, knockout mutants of MET18 are viable in yeast (Kou et al, 2008) and without obvious phenotypic changes in Arabidopsis ( Figures 5M and 5N), although in mouse MMS19 knockout is embryonic lethal (Gari et al, 2012). It was reported that Met18 and MMS19 have the ability to bind directly to target apoproteins for Fe-S cluster assembly (Gari et al, 2012;Stehling et al, 2012), and depletion of MMS19 caused a decrease in protein level of MIP18, suggesting that MMS19 is critical for the stability of MIP18 (Gari et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…1, A and B). Studies in yeast suggest that MMS19 deficiency affects the general transcription level in human cells (3,8). Thus, we examined the mRNA levels of Fe-S helicases in MMS19-deficient cells.…”
Section: -E)mentioning
confidence: 99%
“…Yeast Mms19 itself apparently does not participate directly in NER because it is not required for a reconstituted in vitro NER system (7), but recent studies by Kou et al show that yeast Mms19 functions indirectly in NER by maintaining an adequate cellular concentration of the TFIIH subunit Rad3, a yeast counterpart of human XPD. However, the temperature-sensitive growth defect of mms19 is not rescued by artificially maintaining an adequate amount of Rad3, indicating that yeast Mms19 serves as a multifunctional regulator in the maintenance of genome integrity (8).…”
mentioning
confidence: 99%